Strategic positioning of marketplaces and learning institutions as digital village centers for rural empowerment and development in Bondo district. - Obare, George .O; Hayombe, Patrick O.; Rabah, Kefah (International Journal of Business and Social Research, 2013)
Digital villages have been identified in Kenya as a solution to internet access problems for the rural areas. However, locations of digital villages with respect to community access was a subject of study in this work. The author set out to illustrate that Digital Villages like other social service centers requires centrality and spatial equity in order to optimize accessibility by community members. Studies have shown that the initial cost of setting ICT internet infrastructure for digital villages is very expensive and this has kept most learning institutions and marketplaces almost entirely inaccessible especially in the rural areas of Kenya. This research has made efforts assess the infrastructure that supports the Digital village services in Bondo District. The central aim was to identify hotspots and suitable areas in the district that can serve as convenient sites for digital villages. Geographical Information System ArcGIS 10 and Multi Criteria Decision Analysis tool; Analytical Hierarchy Process has been used to create suitability maps. Ranking of infrastructure of learning institutions was used. The first step utilized infrastructure ranks based on International Union indicators of ICT access for education. Suitability maps were then developed showing optimal prediction areas for location of Digital Villages in Bondo District. Site maps of marketplaces and Learning Institutions were prepared and analyzed using Geographical Information System. Spatial Analysis tools namely; Buffering, Map Overlays and point Interpolation as proximity tools were used to assess the Spatial Qualities of Potential Digital Village Sites. Results reveal that certain institutions are more strategically positioned than others hence more suitable. Spatial Analysis was done based on three divisions namely Maranda, Nyang'oma and Usigu. Most suitable areas falls around Maranda high school, Bondo University and Nyang’oma Technical Institute. The study recommends an integrated policy framework customized to the needs of Bondo District that can stimulate infrastructural development, encourage Public Private Participation, create Community Awareness towards the use of Digital Villages to stimulate socio economic development of the area.
Keywords: Market place; Strategic positioning; Digital villages; Learning Institutions.